Government intervention and institutional trading strategy: Evidence from a transition country - Yi Yao; Rong Yang; Zhiyuan Liu; Iftekhar Hasan (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
This study investigates the effectiveness of government intervention in rescuing bearish markets in a transition economy. Focusing on a pre- and a post-intervention period, the findings reveal that government intervention successfully rescued bearish markets in China and led to a fundamental change in institutional trading strategy after the intervention. We observe that following an intervention, institutions are more sensitive to long-term stock market regulations, whereas individual investors are more concerned about the rules related to their short-term interests. Evidence suggests that a credible signal from the government can be helpful in creating a positive outcome in the market (Bhanot and Kadapakkam, 2006). The findings are important to the current debate regarding the role of govern-ment intervention in markets in other transitional economies, as well as in developed countries.
URN:NBN:fi:bof-201408072063
Keywords: G15; G18; G32; 330; Government Intervention; Institutional Trading Strategy